RELATIONSHIP OF FACTOR-FACTOR WITH EARLY PREGNANCY IN WORKING AREA PUBLIC HEALTH CENTER GUGUK PANJANG - evi hasnita (Universitas Fort De Kock, 2016)
According to the Bureau of Statistics survey in 2012 in Indonesia was 48 / 1,000 pregnancies at the age of 15-19, while in 2007 was 8.5% of pregnancies at age <20 years. Public health center Guguk Panjang 20% of women with risk pregnancies with child-bearing age <20 years. This study aims to determine the factors associated with Pregnancy Early in Puskesmas Guguk Panjang . This type of research is descriptive analytic with cross sectional approach. The population in the study were all pregnant women in Public health center Guguk Panjang. Retrieval using random sampling techniques to obtain 100 respondents. Data collected by using a questionnaire. Data analysis included univariate and bivariate analysis using chi-square test. Results showed 60% of respondents are highly educated, 57% of respondents with high economic status, 52% of respondents with negative behavior, 62% of respondents with a social and cultural good, 75% of respondents affected by the mass media, and 52% of respondents underwent teen pregnancy. The results of the bivariate analysis showed that there is a relationship of education (p = 0.003, OR = 3.857), the economy (p = 0.018, OR = 2.893), behavior (p = 0.003, OR = 3.821), sociocultural (p = 0.01, OR = 3.261) and the media (p = 0.011, OR = 4.030) with a teen pregnancy. It can be concluded that education, economic status, behavioral, social, cultural, and media associated with teen pregnancy. For the expected role of the various parties to raise public awareness, especially young women about the risks of pregnancy at an early age so that young women are not affected by various factors that may increase the risk of teen pregnancy and teen daughter was able to behave avoid the incidence of pregnancy early age.